Pro Apache XML - Sarang, Poornachandra. (Apress : Imprint: Apress, 2006)
Pro Apache XML thoroughly introduces several subprojects found under the Web Services–driven API umbrella. The book begins with a concise introduction to XML and Web Services. Subsequent chapters devote themselves to specific subprojects covering their purposes, APIs, implementation, and practical uses through appropriate code examples. Additional material includes Introductions to several of the Apache Foundation's hottest projects, including Xerces, Axis, and Xindice Building XML–driven websites using the popular Cocoon project Transforming XML–based documents into a variety of formats, including PDF, SVG, and PS, using the Formatting Objects Processor (FOP) project You'lll learn to perform tasks like validation, parsing, transformation, and storage and how to work with this information through a programming interface. You may either read this book from cover to cover or jump to any desired subproject for a detailed study of its implementation. All programming examples use the Java programming language.